IoT based light intensity and temperature monitoring system for plants. (2020) - Swapna, B.; Andal, C.; Manivannan, S.; JayaKrishna, N.; Rao, K. Samba Siva
Abstract: Smart device was developed to measure Intensity of Light and Temperature using LDR and LM35 IC Sensors. The principle is when light falls on the sensor, it changes the resistance of sensor changes which is then converted to change in voltage. The ADC pins on Bolt Wi-Fi Module convert this analog voltage level to digital values. LM35 is the sensors which senses the temperature of environment and based on its value it generate analog output voltage. This analog voltage by the LM35 is then given as input to Bolt A0 pin. The Bolt then converts the analog value to a 10 bit digital value that varies from 0 to 1023. This digital data is sent to the cloud through Bolt device.